Justice is not relative in the global community - Jafar Javan (Freedom from Fear, 2018)
What does really justice mean? Is there a justice for all? The etymology associates the word justice to righteousness, equity and just behaviour. Over the centuries, justice has been always considered as a central virtue to both the moral and political dimensions of societies. Despite the many – and sometimes opposite – interpretations, justice should be aimed at establishing balance among powers and societal order. Justice is the litmus test for the well being of the community as well as for the conduct of its governors.